College Students' Perceived Self-efficacy and Use of Information and Communication Technologies in EFL Learning - Ngo, Hong; Eichelberger, Ariana (International journal of education and development using information and communication technology, 2021)
This study examines Vietnamese, non-English major college students' perceived self-efficacy and their comfort in using information and communication technologies (ICTs) in learning English as a foreign language. A survey was completed by 975 students. Findings revealed that half of the students ranked themselves as basic EFL users, and fewer rated themselves as independent users or proficient users. Inferential statistics analysis found students' perceived self-efficacy differed by their comfort levels in using ICTs. Specifically, those with a high to very high comfort level were more self-efficacious in their learning of English compared to those with an average or low level. These findings may help explain the issue of limited proficiency in EFL learning among non-English major college students in Vietnam, in relation to how comfortable they are using ICTs. Further investigation is needed however to clarify the relationship between technology comfort levels and self-efficacy among EFL learners.